THE EFFECT OF VISUALIZATION STRATEGY ON THE STUDENTS’ READING COMPREHENSION AT SMA SWASTA NURCAHAYA MEDAN - Juan Carlos Tanjung; Madina Madina; Muhammad Muslim Nasution (ELT (English Language Teaching Prima Journal), 2022)
The aim this research was to get the information about the effect of Visualization straregy on the students reading comprehension who were from SMA Swasta Nurcahaya Medan at school year 2022/2023. Quantitative method was applied in carrying out this research. After carrying out the research, the writer got research findings. Visualization strategy has given significant impact on the students’ reading comprehension. From the research result, it was known that the implementation of Visualization Strategy is more effective than conventional teaching strategy in teaching reading comprehension. The writer did the pre-test. From the pre-test it can be seen that 66.90 were the mean scores of the students who came from control class. The writer did the post-test to the students who were control class. The mean scores of the students were 74.28. Meanwhile, the writer also got the data from the experimental class. After doing pre-test in the experimental class, it can be seen that the mean scores of the students were 67.57. After doing the post-test, it can be seen that the mean scores of the students were 85.81. The writer compared the mean scores of the students who were from the control class and the experimental class. The mean scores were compared after doing the pre-test and the post-test. From the result of the post-tests, the writer could make conclusions. The students’ mean scores from the experimental class were higher than the students’ mean scores from the controlc class (85.81>74.28). The difference of mean scores were 11.53. The writer implemented t-test in carrying out this research. After doing the test. it was known that t-observed value was 5.67. After seeing the result, t-test (5.67) was higher than the t-table (1.675) (p = 0.05 and df = 56). By seeing this data, the writer concluded that Visualization Strategy significanlty affected the reading comprehension of the students who were from SMA Swasta Nurcahaya Medan. Keywords: The Effect, Visualization Strategy, Reading Comprehension, Descriptive Text